2010
DOI: 10.2166/wh.2010.102
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of antibiotic resistance genes in reclaimed water and river water in the Werribee Basin, Australia

Abstract: The purpose of this study was to investigate the occurrence of antibiotic resistance genes (ARGs) in water used for irrigation in the Werribee River Basin, Australia, including river water and reclaimed effluent water (reclaimed water). Samples of reclaimed water, collected over a oneyear period, were screened for the occurrence of ARGs using PCR detection assays. The presence of ARGs in the reclaimed water samples were contrasted with that of water samples taken from the Werribee River Basin, collected ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…ARGs or bacteria expressing ARGs corresponding to resistance to aminoglycoside, beta-lactam, chloramphenicol, fluoroquinolone, lincomycide, linezolid, lipopeptide, macrolide, sulfonamide, tetracyclines, and vancomycin antibiotics have been previously identified in recycled water or environments directly impacted by irrigation, infiltration, or groundwater recharge using recycled water. [122][123][124][125][126][127][128] Since antibiotic resistance is a natural phenomenon inherent among many bacteria, studies that compare these abundances to relevant control environments, such as corresponding potable water or environments unimpacted by recycled water are of particular value. While the nature of reusing human wastewater means that prior to treatment, human pathogens or other bacteria carrying ARGs will be enriched compared to other source waters, multiple studies have demonstrated that ARGs are often not removed during treatment, and in some cases, are even amplified.…”
Section: Antibiotic Resistance Genesmentioning
confidence: 99%
“…ARGs or bacteria expressing ARGs corresponding to resistance to aminoglycoside, beta-lactam, chloramphenicol, fluoroquinolone, lincomycide, linezolid, lipopeptide, macrolide, sulfonamide, tetracyclines, and vancomycin antibiotics have been previously identified in recycled water or environments directly impacted by irrigation, infiltration, or groundwater recharge using recycled water. [122][123][124][125][126][127][128] Since antibiotic resistance is a natural phenomenon inherent among many bacteria, studies that compare these abundances to relevant control environments, such as corresponding potable water or environments unimpacted by recycled water are of particular value. While the nature of reusing human wastewater means that prior to treatment, human pathogens or other bacteria carrying ARGs will be enriched compared to other source waters, multiple studies have demonstrated that ARGs are often not removed during treatment, and in some cases, are even amplified.…”
Section: Antibiotic Resistance Genesmentioning
confidence: 99%
“…The ARGs will neutralize the benefit antibiotics once given to human beings (Baker ; Hiltunen et al ). Compared with drinking water and rivers, there are more resistant genes and types existing in reclaimed water (Barker‐Reid et al ; Fahrenfeld et al ; Wang et al ), urban waste water, leachate treatment plant and treatment plants (Schwartz et al ; Shakibaie et al ; Luprano et al ; Tang et al ; Zhang et al ), livestock and fishing water (Chen et al ; Frey et al ; Xiong et al ; He et al ; Jia et al ; Cui et al ). ARGs like tetA , tetB , tetC , tetW , tetX , tetG , tetM , tetO , tetS , tetQ , tetP , tetG , sul 1, sul2 , sul3 , blaTEM , qnrA , AmpC , mefA , aacC1 , strA , ermB , cmlA5 , vanA , dfrA1 , qepA , oqxA , oqxB , cat , cml , bla , aacA , aph , aadA , mecA , intI1 , might contribute to the dissemination of antibiotic resistance among pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the wastewater treatment process reduced the mecA concentrations, which can partly be explained by removal of biomass, but did not completely eliminate the mecA gene from the effluent (Börjesson et al 2009b). Barker-Reid et al (2010) studied the occurrence of ARGs in water used for irrigation in the Werribee River Basin, Australia, including river water and reclaimed effluent water. Samples were collected over a one-year period and screened for the presence of ARGs by PCR.…”
Section: Tet(o) Tet(q) Tet(w) Tet(c) Tet(h) and Tet(z)mentioning
confidence: 99%
“…The low detection of ARGs in river water indicated that, regardless of its poor water quality, the river has not yet been severely contaminated with ARGs. The authors also concluded that the greater prevalence of ARGs in reclaimed water indicates that this important agricultural water source will need to be extensively monitored in the future (Barker-Reid et al 2010). Picão et al (2008) searched for plasmid-mediated quinolone resistance genes ( qnr) among waterborne environmental Aeromonas spp.…”
Section: Tet(o) Tet(q) Tet(w) Tet(c) Tet(h) and Tet(z)mentioning
confidence: 99%